Stock prices and foreign exchange rates : the case of Iceland, Norway, Sweden and Hungary - Albert Þór Guðmundsson 1988- (2014)
The relationship between domestic stock prices and real exchange rates in Iceland, Norway, Sweden and Hungary is studied using two different methodologies. What makes this study unique is the fact that all four countries are small European countries with independent currencies. Previous studies have focused mainly on emerging markets. The sample period under analysis is Jan 2003 – Jan 2014. The sample period for Iceland is divided into two sub-periods representing periods pre- and post capital controls. A co-integration method is used to examine the channels for the dynamic linkage of the relationship. Additionally, a dynamic conditional correlation (DCC) method is used to estimate the source of the dynamic relationship with regards to the US market. The empirical results suggest a co-integrated relationship between domestic stock prices and real exchange rates. When comparing results between the two sub-periods for Iceland a stronger co-integrating relationship is detected in the state of capital controls. A significant time-varying correlation is established but the driving force of the relationship cannot be determined. In other words, no “clean” channels are established as a linkage for the co-integrating relations.